Hubungan Merokok dan IMT dengan Kejadian Hipertensi pada Laki-Laki Dewasa di Desa Alassumur Lor Kecamatan Besuk Kabupaten Probolinggo - Intan Dewi Irfanda; Ainul Yaqin Salam; Alwin Widhiyanto (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
Hypertension or high blood pressure is defined as a continuous increase in blood pressure that exceeds normal limits (Nuraini et al., 2023). Hypertension occurs due to several factors, the first being modifiable and non-modifiable factors. Among the modifiable risk factors for hypertension are smoking and obesity. People who smoke more than one pack of cigarettes per day will be twice as vulnerable as people who do not smoke (Luh et al., 2020). The purpose of this study was to determine the correlational between smoking and BMI with the incidence of hypertension in adult men in Alassumur Lor Besuk Probolinggo. The research design used an Correlational Analytic with a cross-sectional approach. The population in this study was 35 with a total sampling technique. The research instrument used a questionnaire, then the data obtained will be tested by Spearman rank. The results of the study obtained the smoking variable ρ = 0.018, the BMI variable ρ = 0.071. This shows that there is a corelation between smoking behavior and BMI with the incidence of hypertension. Smoking behavior that is increasingly uncontrolled will cause hypertension and accumulation of fat on the walls of blood vessels can cause narrowing and hardening, increasing blood flow resistance and ultimately increasing blood pressure. It is hoped that respondents will reduce their smoking habits and start a healthy life by maintaining a diet, exercising regularly and eating nutritious foods.